THU0225 The progression of lung involvement in rheumatoid arthritis patients receiving biological therapies. (12th June 2018) - Yalçınkaya, Y.; Can, M.; Karakurt, S.; Coşkun, N.; Albayrak, E.; Mursaloglu, H.; Topcu, A.; Demir, M.; Dalkılıc, E.; Inanc, N.
Abstract : Background: Lung involment is one of the extra-articular manifestations that is shown to be related to morbidity and mortality in Rheumatoid arthritis (RA). Objectives: We evaluated the progression of lung involvement in RA patients receiving biological treatment. Methods: Eighty RA patients fulfilling ACR/EULAR classification criteria (2010) receiving biologics who had high-resolution computerised tomography (HRCT) of chest within 6 months of respiratory symptoms (cough/dyspnea) and/or any pathology in chest radiography were included. Warrick score, evaluating alveolitis and fibrosis, was calculated in RA patients by using HRCT of chest. Results: The demographics and clinical findings were summarised in table 1. In 29 RA patients with interstitial findings in HRCT of chest; 7 (24%) were regressed and 1 (4%) was progressed with biologic drugs. Findings of alveolitis and fibrosis were completely regressed in 2, only alveolitis component was completely regressed in 3 and partially in 2 patients. The patient who progressed had new findings of alveolitis (table 2). Twenty-one patients in whom Warrick scores did not change, 5 received rituximab (RTX) and 10 received TNF inhibitors (TNF-inh). The mean Warrick scores was improved after biologics (11, 3±9 (3–30) vs 10, 3±9 (0–30), p=0, 035). The improvement in alveolitis scores was significant (2, 1±1, 6 vs 1, 5±1, 6, p=0, 031) while fibrosis scores were not (9, 2±7, 7 vs 8, 8±8). Initial and control Warrick scores were higher in RTX receivers (16±9 vs 9, 2±8, p=0034 and 14, 8±10, 1 vs 8, 4±8, 1), but the improvement after biologics was not different. Conclusions: This study revealed an improvement in alveolitis after biologic drugs in RA patients. Fibrosis was not found to be effected by therapy. Lung lesions were improved in both RTX and TNF-inh groups. Disclosure of Interest: None declared